Intervensi biskuit tempe kurma bagi peningkatan status gizi balita penderita tuberkulosis - Fatmah Fatmah (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Weight gain as an indicator of nutritional status during tuberculosis drugs management has a significant relationship with the rapid conversion of sputum smear, low incidence of relapse and duration of anti tuberculosis drugs in patients with tuberculosis. Low intake of food in patient suffering from an infectious disease is caused by the emergence of anorexia, nausea, vomiting, and increased body temperature. Inadequate nutrient intake affects the immune system, lower resistance to infection and slow healing resulting progressive tuberculosis (TB).Objective: To assess the effect of tempeh dates biscuit consumption on the change of nutritional status of tuberculosis preschoolers patients.Method: A quasi-experimental design towards 52 under five children with TB status and who were underweight was done in all sub-districts at Depok City. There were three groups participated in the study i.e tempeh dates biscuits as intervention group, and two groups of control (tempeh and placebo biscuits). The nutritional status of subjects was assessed each biweekly by giving daily 50 grams of biscuits within four weeks. Data analysis was using paired t-test and Anova.Results: There was greatest weight gain in a subject who received tempeh dates biscuit by 0.5 kg and largest height improvement in the tempeh biscuits group by 1.8 cm. Weight, height and z-score weight/age had significant differences in the three groups at the end of the study. There were significant differences in carbohydrate intake in the intervention group at pre and post-intervention. The tempeh biscuits group had different levels of mothers’ knowledge on nutrition and TB at the end of the study.Conclusion: Tempeh dates biscuit can be recommended as an alternative supplementation feeding program for TB and non-TB under five children with underweight status.